Evaluasi Kepuasan Konsumen Dalam Meningkatkan Pelayanan Dengan Menggunakan Metode Servqual dan Kano (Studi Kasus di PT.Daya) - Dini Yulianti; Wawan Darmawan (Universitas Insan Cendekia Mandiri, 2021)
PT. Daya is one of the actors in the automotive and service sector that can maintain the quality of service to customer satisfaction where the business competition faced by companies increasingly requires company management to be more careful in determining marketing strategies in order to win increasingly competitive competition. At this time products in the form of services have become a fairly dominant part of its influence in the economy, in addition to physical queuing products where business competition faced by companies increasingly demands management to be more careful in determining strategies in order to win increasingly competitive competition. From the purpose of this study to find out or find the value of the results of the actual performance GAP attribute with customer expectations, so that it will be known how much the level of service satisfaction has been provided to customers and provide alternative solutions for improvement. The method used is the Service Quality and Kano methods. The results obtained in this study are Kano for the Indiffrent category, the highest score is from the respondent's results, and the lowest value is on reverse and one dimensional. Then in Service Quality (Servqual) there is the highest value on the value of the inadequate capacity of the workshop area, GAP 0.43 and Mechanics are not responsive to consumer willingness, the smallest value is GAP 0.00 for the Service Quality (Servqual) category.